Crystal structure, Hirshfeld surface analysis and contact enrichment ratios of 5, 5-dimethyl-2-(2, 4, 6-tris(trifluoromethyl)phenyl)-1, 3, 2-dioxaborinane. Issue 1 (13th August 2022) - Amarne, Hazem; Helal, Wissam; Taher, Deeb; Korb, Marcus; Al-Hunaiti, Afnan
Abstract: The title compound C14 H12 BF9 O2 (1 ) was obtained as the sole product during a failed attempt to make a new organoboron compound. Characterization of the title compound by NMR ( 1 H, 13 C 1 H, 19 F 1 H, and 11 B) spectroscopy and single crystal X-ray diffractometry confirmed the formation of 1 . Compound 1 crystallizes in the triclinic space group P -1, with a = 8.275(5) Å, b = 8.611(5) Å, c = 10.910(5) Å, α = 89.634(5)°, β = 89.637(5)°, γ = 87.403(5)°, V = 776.6(7) Å 3, and Z = 2. The intermolecular interactions in 1 were analyzed using the Hirshfeld surface method including 2 D fingerprint plots and enrichment ratios ( E ), which shows that the most favorable intermolecular contacts are the Cπ ···F–C and C–H···F–C interactions. The interaction energies between molecular pairs revealed the importance of these weak non-covalent interactions in stabilizing the molecular structure of 1 . The title compound was also studied by DFT calculations and UV-Vis spectroscopy.